Relation of Specialization of Agrarian Sector to Distribution of Labour Costs in Connection with Seasonality of Agricultural Work - Manasyan, Volodya (Bulletin of Yerevan University G: Economics, 2013)
The labour costs in general subindustries of agricultural production and issues on distribution of labour resource in connection with seasonality of agricultural work are scrutinized in the article. It is especially strongly displayed on conditions of big variety of agro-climatic resources of different high-rise landscape zones of the Republic of Armenia. Based on this structure of labour costs of the republic, it is fixed that about 85% of total labour costs and for particular ones more than 15% is expended in horticulture and animal husbandry (together with forage) for cultivation of cultivated crops and other planting. This indicates that farms are specialized in production of grapes, fruits and production of animal husbandry. However, it doesn’t mean that also intraeconomic specialization is as legible, as majority of them has nearly all specified subindustries, which is not often justified from social-economic viewpoint.